Assessment of the potential of floating solar photovoltaic panels in bodies of water in mainland Spain. (15th March 2022) - López, M.; Soto, F.; Hernández, Z.A.
Abstract: This article presents the potential of floating photovoltaic solar energy in Spain, a country with a high solar energy resource and a large water surface area for its deployment, for the first time. Geodata for natural, artificial, and highly modified bodies of freshwater, along with environmental geospatial datasets, were used to calculate electricity generation, taking into account the positive water-cooling effect. The results revealed that Spain could meet about 31% of its electricity demand by covering only 10% of the available water surface area. Deployment of the country's full floating photovoltaic potential could reduce non-renewable electricity generation by 81% and greenhouse gas emissions by 6%, thereby helping to meet the European Union 2030 target. Spanish regions could benefit from this renewable energy, not only by reducing their dependence on non-renewable resources, but also by balancing their electricity generation and demand. The potential of this renewable energy technology is higher in southern regions and particularly in Extremadura, where the electricity generation potential is three times the electricity demand. A detailed analysis of the floating photovoltaic potential in three dam reservoirs, the Borbollón, La Pedrera and Guadalcacín, is also presented for four coverage scenarios. The results highlight the importance of including water depth restrictions on floating photovoltaic module operation and variations in reservoir water level in future assessments, rather than simply applying a fixed percentage of coverage. Highlights: Spain could meet 31% of its electricity demand with 10% FPV cover of water surface. Harnessing the FPV potential of Spain could reduce non-renewable electricity by 81%. Harnessing the FPV potential of Spain could reduce GHG emissions by 6%. Costs of FPV systems should be reduced to achieve a competitive LCOE in Spain. Water depths and water level variations must be considered in future assessments.